The Effect of Work Life Balance and Compensation on Employee Performance with Job Satisfaction as a Mediating Variable in Gen Z Employees - Lestari, Sri Katrina Bangnga; Fikri, Aula Ahmad Hafidh Saiful (Formosa Journal of Sustainable Research, 2024)
This study examines the impact of work-life balance and compensation on employee performance among Generation Z employees at Bento Kopi Yogyakarta, using job satisfaction as a mediating variable. Employing a descriptive quantitative approach with purposive sampling of 150 employees, the research utilized Partial Least Square (PLS) analysis through SmartPLS 3 software. Findings reveal positive significant relationships: work-life balance and compensation positively influence job satisfaction, which in turn significantly affects employee performance. The study demonstrates partial mediation of job satisfaction between work-life balance and compensation with employee performance, providing insights into workforce dynamics for Generation Z